A review on research progress of machining technologies of carbon fiber-reinforced polymer and aramid fiber-reinforced polymer. (July 2019) - Shi, ZY; Cui, P; Li, X
Since the application of fiber-reinforced polymer continues to expand, the demands of product quality for secondary cutting process are becoming increasingly higher to ensure the accurate coordination, connection, and assembly. There are some defects such as tearing, burr, delamination, and thermal damage after secondary cutting process, which limit the further applications of the materials. It is urgent to carry out comprehensive research on the secondary processing technology. In this paper, the fiber-reinforced composites' category, characteristics, and their applications were first described. Then the cutting performances, the causes of machining defects, and machining mechanisms have been analyzed. Finally, different compound processing methods, their characteristics, and applications have been elaborated. The most common forms of compound processing method including combined machining of cutting and grinding, ultrasonic vibration–assisted machining, and low-temperature–assisted machining have been covered in this paper. Results show that the compound processing method is the most effective way for improving the second processing quality of fiber-reinforced polymer. More machining mechanisms and applications of compound processing method need further experimental research. The barriers and future in the fields of research on machining of fiber-reinforced composites have been analyzed in this paper.